As Artes e as Técnicas na produção dos vinhos cistercienses de Alcobaça. Uma abordagem em torno do Inquérito da Real Academia de Ciências de Lisboa de 1787 - Maduro, António (2015)
The survey “Questions Directed to the Tenants of Agriculture of Portugal” held by the Academy is an essential document to characterize seventeenth century farming. Twenty-three out of 193 questions are focused on vineyard and wine, which represents about 12% of the survey and highlights the importance of this product in the realm’s economy. We intend to clarify the geography and development of Cistercian vineyard of agricultural areas in Alcobaça, the developing work on the vineyard, the regime of manorial monopoly of wine production and its effects, characterizing the vineyard, the art and craft of wine production, its several types, quality wine conservation criteria, wine usage and its by-products.